Konstruksi Sosial Partisipasi Masyarakat Adat Dayak Deah dalam Pengelolaan Dana Desa - Ruli Ananda; Budi Suryadi; Deasy Arisanty; Muhamad Rusmin Nuryadin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study employs a qualitative research approach to explore the social construction of participation by the Dayak Deah indigenous community in the oversight of village fund management in Pengelak Village, Upau Sub-District, Tabalong Regency. Data were collected through participant observation, in-depth interviews, and focus group discussions with key informants. The findings reveal that participation by the Dayak Deah community is deeply rooted in cultural values and local identity, reflecting a strong sense of collective responsibility for environmental stewardship and community development. Traditional practices such as gotong royong (cooperation) are central in shaping their involvement. Participation is influenced by three interrelated dimensions: cultural and communal values, which reflect indigenous norms and shared heritage; social and institutional structures, particularly the role of traditional leadership and customary institutions; and communication and knowledge systems, including interaction patterns, access to information, and levels of education. Additionally, historical experiences with governance, development interventions, and resource management shape the community’s trust in participatory mechanisms. In conclusion, the Dayak Deah indigenous community's participation in village fund supervision results from a complex interplay of cultural traditions, institutional arrangements, communication practices, educational factors, and historical context. Understanding these socially constructed dimensions is essential for developing inclusive and sustainable strategies to strengthen community-based governance.